The Determination and Performance Evalution of Slurry System in Haita Region - Fan, Zhen Zhong; An, Hui Ming; Liu, Qing Wang; Wang, Ji Gang (Applied Mechanics and Materials, 2014)
For the unique geological features in Haita area, we optimized the synthesis conditions of slurry fluid loss additive ZJK103 and evaluated its performance. The experimental results showed that under different water conditions, water quality had no effect on fluid loss of ZJK103; The fluid loss additive had no adverse impact on compressive strength of cement stone; With same mixing water and different conserving water, the compressive strength did not change much. ZJK103 had better thickening effect than other average fluid loss additives. According to the performance of slurry system, the indoor synthetic slurry filtrate reducer could meet the quality requirements of Haita region cementing.